1998
DOI: 10.1002/lt.500040404
|View full text |Cite
|
Sign up to set email alerts
|

Late hypertension after liver transplantation: A comparison of cyclosporine and tacrolimus (FK 506)

Abstract: Hypertension frequently develops early after liver transplantation when cyclosporine-based immunosuppression is used. However, initial experience with tacrolimus has suggested that its use leads to a lower early incidence of hypertension. In this study, the blood pressure status of patients treated with cyclosporine (n ‫؍‬ 131) and those treated with tacrolimus (n ‫؍‬ 28) was compared 24 months after liver transplantation. At this time interval, the prevalence of hypertension in the cyclosporine and tacrolimus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
6

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 24 publications
2
63
0
6
Order By: Relevance
“…[1] Studies including liver transplant recipients revealed that cyclosporine immunosuppression is associated with a higher likelihood of post-transplant weight gain compared with tacrolimus. [13] Our data reporting an increase of serum triglyceride and LDL cholesterol levels and a decrease of serum HDL levels in cyclosporinetreated patients support post-transplant dyslipidemia. We agree that conventional coronary risk factors in the posttransplant setting should be identified and managed aggressively to decrease the cardiovascular morbidity and mortality in this high-risk population.…”
Section: Discussionsupporting
confidence: 60%
“…[1] Studies including liver transplant recipients revealed that cyclosporine immunosuppression is associated with a higher likelihood of post-transplant weight gain compared with tacrolimus. [13] Our data reporting an increase of serum triglyceride and LDL cholesterol levels and a decrease of serum HDL levels in cyclosporinetreated patients support post-transplant dyslipidemia. We agree that conventional coronary risk factors in the posttransplant setting should be identified and managed aggressively to decrease the cardiovascular morbidity and mortality in this high-risk population.…”
Section: Discussionsupporting
confidence: 60%
“…15 Similar variability has been described for such indicators of morbidity as infection, rejection, renal impairment, graft survival, and length of hospital stay. Even in studies in which there were no differences in mortality, diabetics more often experienced bacterial, 13,40 viral, 13 and fungal 13,40 infection, renal impairment, 40 and episodes of rejection 17 and steroid-resistant rejection 19 than nondiabetics. Among the other possible adverse effects of diabetes in transplantation has been the suggestion of an increased frequency or rapid progression of diabetic nephropathy in type 1 insulindependent diabetic recipients.…”
Section: Impact Of Diabetes On the Outcome Of Liver Transplantationmentioning
confidence: 91%
“…The other immunosuppressives (azathioprine, mycophenolate mofetil, and sirolimus) are not diabetogenic. The diabetogenic potential of tacrolimus appears to be greater than that of cyclosporine in renal transplant patients, 30 whereas they appear equal in liver transplant recipients, 19,31,32 even though a change from tacrolimus to cyclosporine can completely reverse tacrolimus-induced diabetes in the occasional patient. 33 …”
Section: Prevalence Of Diabetes In Liver Transplant Recipientsmentioning
confidence: 99%
See 2 more Smart Citations